TRENDS IN THE IMPLEMENTATION OF A GAMIFIED FOREIGN LANGUAGE LEARNING SPACE IN MODERN CONDITIONS - Krekoten, Olena (SWorldJournal, 2025)
The article aims to analyze existing approaches to the implementation of gamified environments in university-level foreign language courses (English or French as a second foreign language) and to develop a practical strategy for their integration within t